Bactericidal effects of propolis/polylactic acid (PLA) nanofibres obtained via electrospinning - Sutjarittangtham K. (International Bee Research Association, 2014)
Electrospinning of propolis / polylactic acid (PLA) fibres was investigated for propolis concentrations from 0-10% (w/v). Solutions could not be spun when the amount of propolis was over 8% (w/v). Mechanical characterization indicated that propolis reduced the tensile strength. The fibre mats exhibited poorer mechanical performance when the propolis concentration was increased. At propolis concentrations of 2-6% (w/v), the fibres were smooth, bead-free and homogeneous. When the concentration of propolis was more than 6% (w/v), the fibres changed from ductile to brittle. The fibres containing 2% (w/v) propolis showed bactericidal effects on Staphylococcus aureus, Staphylococcus epidermidis, Proteus mirabilis and Escherichia coli. At a propolis concentration of 4% (w/v) they also inhibited Bacillus cereus. © IBRA 2014.